Primary shunt hyperbilirubinaemia: a variant of the congenital dyserythropoietic anaemias. Issue 786 (April 1991) - Bird, A. R.; Knottenbelt, E.; Jacobs, P.; Maigrot, J.
Abstract : A 19 year old Mauritian male presented with episodic nausea, abdominal discomfort and jaundice. Unconjugated hyperbilirubinaemia and erythroid hyperplasia without dyserythropoiesis led to the diagnosis of primary shunt hyperbilirubinaemia. The similarity between congenital dyserythropoietic anaemia and this entity suggests that patients with these lesions can be considered within a single spectrum of disorders, characterized as congenital ineffective erythropoiesis.